Our Scientific Journey through the Ups and Downs of Blood Glucose Control in the ICU - Van den Berghe, Greet; Vanhorebeek, Ilse; Langouche, Lies; Gunst, Jan (American journal of respiratory and critical care medicine, 2024)
This article tells the story of our long search for the answer to one question: Is stress hyperglycemia in critically ill patients adaptive or maladaptive? Our earlier work had suggested the lack of hepatic insulin effect and hyperglycemia as jointly predicting poor outcome. Therefore, we hypothesized that insulin infusion to reach normoglycemia, tight glucose control, improves outcome. In three randomized controlled trials (RCTs), we found morbidity and mortality benefit with tight glucose control. Moving from the bed to the bench, we attributed benefits to the prevention of glucose toxicity in cells taking up glucose in an insulin-independent, glucose concentration gradient-dependent manner, counteracted rather than synergized by insulin. Several subsequent RCTs did not confirm benefit, and the large Normoglycemia in Intensive Care Evaluation-Survival Using Glucose Algorithm Regulation, or "NICE-SUGAR," trial found increased mortality with tight glucose control associated with severe hypoglycemia. Our subsequent clinical and mechanistic research revealed that early use of parenteral nutrition, the context of our initial RCTs, had been a confounder. Early parenteral nutrition (early-PN) aggravated hyperglycemia, suppressed vital cell damage removal, and hampered recovery. Therefore, in our next and largest "TGC-fast" RCT, we retested our hypothesis, without the use of early-PN and with a computer algorithm for tight glucose control that avoided severe hypoglycemia. In this trial, tight glucose control prevented kidney and liver damage, though with much smaller effect sizes than in our initial RCTs without affecting mortality. Our quest ends with the strong recommendation to omit early-PN for patients in the ICU, as this reduces need of blood glucose control and allows cellular housekeeping systems to play evolutionary selected roles in the recovery process. Once again, less is more in critical care.